Comparative Persistence of Non-tumor Necrosis Factor - Gu, Phillip; Dube, Shishir; Lee, YooJin; Yang, Shaohong; Li, Dalin; Haritunians, Talin; Vasiliauskas, Eric (Digestive diseases and sciences, 2024)
Background The comparative safety and effectiveness of available biologics for post-operative prophylaxis in Crohn's disease (CD) is uncertain. Drug persistence may serve as a real-world proxy for tolerability and effectiveness. We evaluated the comparative persistence of non-TNF and TNF antagonists for post-operative prophylaxis and their comparative effectiveness for preventing early endoscopic post-operative recurrence (POR). Methods We conducted a single-center, retrospective study of surgically naïve CD subjects undergoing ileocecal or small bowel resection between 1/1/2000 and 12/31/2021 and prescribed a biologic for post-operative prophylaxis. We compared the risk of prophylaxis failure (requiring recurrent surgery or discontinuation of therapy due to persistent POR despite optimized drug level or dose escalation, immunogenicity, and/or adverse event) and early endoscopic POR (Rutgeert's score [greater than or equal to] i2 within 15 months postoperatively) between non-TNF and TNF antagonist prophylaxis using Cox proportional hazard and logistic regression, respectively, adjusting for demographic and disease characteristics. Results The study included 291 subjects (81% TNF antagonists). After multivariable adjustment, non-TNF antagonist prophylaxis was associated with a significantly lower risk of prophylaxis failure than TNF antagonists (hazard ratio 0.26; 95% confidence interval (CI) [0.13-0.53]). Prophylaxis with non-TNF and TNF antagonists had similar risk of early endoscopic POR (odds ratio 0.66; 95% CI [0.32-1.36]). Stratifying the non-TNF antagonists by anti-integrin and anti-IL12/23 yielded similar results. Conclusion In a cohort of surgically naïve CD subjects prescribed a biologic for post-operative prophylaxis, non-TNF antagonists had greater persistence than TNF antagonists with similar risk for early endoscopic POR. If confirmed by large, prospective studies, these findings can inform post-operative management strategies in CD.